Chronic Hepatitis E Viral Infection After Liver Transplantation: A Regression of Fibrosis After Antiviral Therapy. Issue 9 (September 2017) - Mazzola, Alessandra; Tran Minh, Margherita; Charlotte, Frédéric; Hdiji, Aisha; Bernard, Denis; Wendum, Dominique; Calmus, Yvon; Conti, Filomena
Abstract : Abstract: Hepatitis E virus (HEV) infection is increasingly being reported in immunocompromised patients and particularly organ transplant recipients. In this context, HEV infection frequently evolves to chronic infection with a rapid progression of fibrosis to cirrhosis. Ribavirin monotherapy and a minimization of immunosuppression represent the treatment of choice, with a good response rate. However, no data are available on whether treatment can achieve a regression of liver fibrosis in chronic HEV patients. A 57-year-old male patient received a liver transplant for alcoholic cirrhosis and, 6 years later, developed biopsy-proven chronic HEV infection. The patient received different antiviral therapy regimens (pegylated interferon alpha 2b and ribavirin different dosages, and long-term treatment with ribavirin monotherapy still ongoing) but without achieving a sustained virological response. Liver function parameters normalized after 1 month of treatment but without the clearance of HEV. Hepatitis E virus RNA levels also remained detectable in the serum and stools throughout ribavirin monotherapy. No serious adverse events were reported. A gradual regression of liver fibrosis was reported (Metavir A0/F1 in 2015 versus A3/F4 in 2008). Long-term treatment with ribavirin is safe in liver transplant recipients, without achieving HEV sustained virological response, and may induce a biopsy-proven regression of liver fibrosis in a liver transplant recipient with cirrhosis after chronic HEV infection. Abstract : Case report describing biopsy-proven regression of liver fibrosis in a liver transplant recipient with hepatitis-E-related cirrhosis following long-term ribavirin monotherapy without virologic response.